STRATEGI PEGADAIAN SYARIAH DALAM MENINGKATKAN JUMLAH NASABAH - Suharyono Suharyono (JURNAL AGHNIYA, 2020)
Abstract,This study will discuss the strategy of the Islamic financial industry in particular Shariah Pawnshop in increasing customers. Adjustment of appropriate strategies and techniques will greatly determine the sustainability of Shariah Pawnshop. During this time many people who view the Shariah Pawnshop is a place where only accepting gadai services only.practice In industry Shariah Pawnshop there are actually many other financial services products that are developed in Shariah Pawnshop. The purpose of this study is to find out and analyze strategies of Shariah Pawnshop in dealing with the challenges of the industry at the present time. The method used is to use a literature study. The paper provides conclusions on a review of the problems that have been discussed in a study of theories, hypotheses, and theories that support the research conducted. Keywords: Shariah Pawnshop, Strategy, Customer Abstrak,Penelitian ini akan membahas tentang strategi industri keuangan syariah khususnya pegadaian syariah dalam meningkatkan nasabah. Penyesuaian strategi dan tekhnik yang sesuai akan sangat menentukan bagi keberlangsungan pegadaian syariah. Selama ini banyak masyarakat yang berpandangan pegadaian syariah adalah tempat dimana hanya menerima layanan gadai semata. Pada praktek industri pegadaian syariah sebenarnya masih banyak produk-produk jasa keuangan lainnya yang di kembangkan di pegadaian syariah. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis strategi pegadaian syariah dalam mengahadapi tantangan industi pada saat sekarang. Metode yang digunakan adalah dengan menggunakan kajian litelatur. Tulisan memberikan kesimpulan atas tinjauan masalah yang telah dibahas dalam sebuah kajian teori, hipotesis, serta teori-teori yang mendukung penelitian yang dilakukan. Kata kunci: Pegadaian Syariah, Strategi, Nasabah